Forecasting small population monthly fertility and mortality data with seasonal time series methods - Bravo, Jorge Miguel (2020)
Bravo, J. M., & Coelho, E. I. F. (2020). Forecasting small population monthly fertility and mortality data with seasonal time series methods. In W. L. Linhares (Ed.), As Ciências Sociais Aplicadas e a Interface com vários Saberes (Vol. 2, pp. 158-176). Atena. https://doi.org/10.22533/at.ed.79020280112